Benefits of local banking in local economic development: Disparities between micro firms and other SMEs - Meslier, Céline; Rehault, Pierre-Nicolas; Sauviat, Alain; Yuan, Dian (Journal of Banking & Finance, 2022)
This paper provides new evidence on the benefits of local banking. Relying on a unique bank-level lending dataset covering 96 French counties from 2005 to 2013, completed by historical firm-level information on firm's main bank, our results reveal strong heterogeneities in the impact of local banking on SMEs' activity depending on firm size, both at the local market level and the bank-firm level. Bank proximity provides strong benefits only to micro firms, the smallest and most informationally opaque SMEs, through a higher presence of regional banks or of geographically focused banks, in both normal and crisis times. Further, we document an overall positive effect of long-lasting bank-firm relationship on SMEs economic activity in line with the continuation-lending hypothesis. Being loyal to either a regional or a national bank fosters micro firms value added, while this benefit only exists for larger SMEs which are loyal to a national bank. Furthermore, our results reveal a flight to quality phenomenon led by national banks in troubled times.